The Role of Competence as a Mediator in the Relationship between Supervision and Training on Employee Effectiveness - Lines La Gwijangga; Rina Rina; Yusran Adi (Westscience Press, 2026)
This study aims to analyse the effect of supervision and training on employee work effectiveness with competence as a mediating variable at the Regional Disaster Management Agency (BPBD) of Nduga Regency. The approach used is explanatory quantitative with a saturated sampling technique involving all 85 BPBD employees. Data collection was conducted through a questionnaire using a 1–5 Likert scale. Data analysis included validity and reliability tests, linear regression, path analysis, and Sobel's mediation test. The results showed that supervision and training had a positive and significant effect on employee competence. In addition, supervision, training, and competence had a significant effect on work effectiveness. Competence was found to significantly mediate the influence of supervision and training on work effectiveness. These findings indicate that strengthening supervision, improving the quality of training, and developing competence are strategic factors in improving the work effectiveness of BPBD employees in disaster-prone areas such as Nduga Regency. This study has important implications for policy makers in planning human resource development in the disaster management sector.